PERFORMANCE EVALUATION OF THE HEALTH SOCIAL SECURITY PROGRAM IN SOUTH SUMATRA USING VALUE FOR MONEY - Muhamad Irpan Nurhab (Fakultas Pertanian, 2021)
Evaluation of the service performance of the South Sumatra health social security program at Dr. Sobirin Lubuklinggau Hospital using Value For Money measurements. This research includes comparative qualitative research, the data used are secondary data, and data collection techniques in this study using observation methods, interviews, and documentation methods. The analysis method used is a quantitative analysis method. The purpose of this study was to determine the performance of the South Sumatra Health Social Security Program services at Dr. Sobirin Lubuklinggau hospital using the Value For Money method and to determine the impact of late disbursement of funds on the performance of Dr. Sobirin Lubuklinggau hospital. The results of this study show that for the economic level, and effectiveness, Dr. Sobirin Lubuklinggau Hospital achieved quite good results. However, the level of efficiency is still lacking, because based on the results of the efficiency analysis there are still some assessments that have not been maximized or have exceeded the standards set by the Minister of Health of the Republic of Indonesia.